Scheduling dynamic job shop manufacturing cells with family setup times: A simulation study - Armin Klausnitzer; Janis S. Neufeld; Udo Buscher (Logistics Research, 2017)
Heuristics based on dispatching rules are still widely used in practice as methods for effective scheduling systems. Despite the successful development of various novel dispatching rules for traditional job shop scheduling environments, nearly none of these has been applied to cellular manufacturingwithin the last decade. In this paper, we close this gap by implementing novel dispatching rules into twostage heuristics in order to solve group scheduling problems in a job shop manufacturing cell. By a comprehensive simulation study these heuristics are evaluated and compared to established effective dispatching rules. It is shown that in some scenarios new heuristics are capable of leading to superior results compared to previous heuristics with respect to mean flow time, mean tardiness and the proportion of tardy jobs. Besides, several influencing factors for the performance of heuristics are analyzed and statistically evaluated.
Keywords: 650; group scheduling; job shop; cellular manufacture; production logistics; heuristics; dispatching rules; simulation